Crowdsourced bathymetry and its use to support resurvey activity in the North Sea region - Payne, Philip (The International Hydrographic Review, 2025)
Crowdsourced bathymetry (CSB) has received much attention, with the IHO CSB Guidance Document being the culmination of numerous lines of development. While CSB has a part to play in global charting, its widescale use is not without issue and should not be seen as panacea for all areas and usages. The North Sea is a heavily used area with mobile seabed and depths critical to shipping. This paper explores the potential of CSB to support resurvey activity in these critical areas and recommends HOs should remain selective in their use of CSB as a data source for charting and focus on using it as an aid to monitoring.